Šibkost Izraela in moč ženskih likov v Deborini pesmi (Sodniki 5) ter v podobnih slavilnih molitvah - Avsenik Nabergoj, Irena (Edinost in dialog, 2024)
This article analyses the poem of Deborah (Judg 5), one of the oldest examples of Hebrew poetry. Together with an even older form of prayer of praise, the Song of Moses (Exodus 15:1-18), it represents the beginnings of the psalm-prayer genre. It focuses on the analysis of the thematic-motivic and rhetorical elements of Deborah’s poem, which reveal the weakness of the tribes of Israel in comparison with the militarily organised Canaanite kingdoms and the strength of Jewish women in war. We are interested in how the women dealt with weakness, how they demonstrated strength and how they relied on the strength of God. The paper shows how only Deborah, a remarkable female figure of the Old Testament, prophetess, judge and military leader, dared to stand up to the destructive strategy of the Canaanites. By defeating the mighty Canaanite warlord Sisera, she demonstrated her extraordinary power in an area that is actually the domain of men, not women. Jael and Sisera’s mother are also portrayed with irony and other rhetorical figures. In the context of Scripture, Deborah’s original prayer of praise, thanking God for her triumph in war, is only justified by the knowledge that the tribes of Israel had to fight for their survival. A comparative analysis of Deborah's poem shows that the tradition of praise as prayer in connection with various female characters was enriched in the later Old Testament period.